Cognitive Style, Learning Preference and Performance: Theory and Empirics - Kolluru, Mythili (International Journal of Psychosocial Rehabilitation, 2020)
We attempt to explore the association between cognition, learning and performance with theoretical and empirical justification. The study was done on a sample of students pursuing their professional course on Chartered Accountancy in India. Using Allinson and Hayes Cognitive Index as a standard tool, we came out with explicit and implicit recommendation to improvise the pedagogy of professional courses of this kind.